The Characteristics of General Medicine Thesis in Kermanshah University of Medical Sciences during Five Years Periods - Mohammad rasoul Khazaee; Ali Karimi; Mohammad Bagher Heydari; Mozaffar Khazaei (Babol University of Medical Sciences, 2018)
BACKGROUND AND OBJECTIVE: Doing and writing the qualified thesis could be considered as the onset of the research proceeding and formation of academic identity of students. The purpose of this study was to investigate the properties of general medicine thesis at Kermanshah University of medical sciences during 5 years periods (2009-2013). METHODS: In this descriptive-analytic (cross-sectional) study, a comprehensive information form was prepared according to previous data. In addition, the contents of all general medicine theses during 2009-2013 (241 cases) were gathered and coded from university library and archive of research center. Data were statistically analyzed using SPSS16 program. FINDINGS: From 241 theses, 204 volumes (84.65%) were related to clinical departments. and 37 cases (15.35%) related to basic departments, and their difference were significant (p=0.000), also difference between clinical departments were significant (p<0.05). The most studies were cross-sectional descriptive (39.42%); 74 (30.7%) cases were performed within 12-18 months; 80 (33.19%) cases were sampled from hospitalized patient files. The most theses (96.68%) were conducted by a supervisor and were dine by one student (96.26%). Further, 189 volumes (78.42%) had statistical advisor. In term of evaluation scoring, 51.86% were scored between 17-18. The most of theses (58.18%) had 30-50 pages. 35.68% had around 10-20 references and 79 cases (32.78%) was published as a paper. CONCLUSION: In spite of the extensive emphasis from educational and research politicians, there is no enough attention to the theses of general medicine courses.